2022
DOI: 10.1101/2022.01.20.477126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The kinase inhibitor Palbociclib is a potent and specific RNA-binding molecule

Abstract: The growing awareness of the role of RNA in human disease has motivated significant efforts to discover drug-like small molecules that target RNA. However, high throughput screening campaigns report very low hit rates and generally identify compounds with weak affinity, while most structures reported in Academic studies also lack the pharmacological properties of successful drugs. Even FDA-approved RNA-targeting drugs have only weak (10 uM) binding activity. Thus, it is often stated that only complex RNA struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This information could be useful to identify RNA off‐targets of known drugs or to design RNA‐targeted molecules from known bioactive scaffolds. The approach of using core RNA‐binding scaffolds to identify targets of FDA‐approved drugs was recently used to characterize palbociclib as a potent binder of the HIV TAR hairpin [39] . A separate approach also recently indicated that protein‐targeting FDA approved drugs similar to known RNA binders can also have RNA‐binding character [40] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This information could be useful to identify RNA off‐targets of known drugs or to design RNA‐targeted molecules from known bioactive scaffolds. The approach of using core RNA‐binding scaffolds to identify targets of FDA‐approved drugs was recently used to characterize palbociclib as a potent binder of the HIV TAR hairpin [39] . A separate approach also recently indicated that protein‐targeting FDA approved drugs similar to known RNA binders can also have RNA‐binding character [40] …”
Section: Resultsmentioning
confidence: 99%
“…The approach of using core RNA-binding scaffolds to identify targets of FDA-approved drugs was recently used to characterize palbociclib as a potent binder of the HIV TAR hairpin. [39] A separate approach also recently indicated that protein-targeting FDA approved drugs similar to known RNA binders can also have RNAbinding character. [40] We also used LASSO logistic regression and neural networks to classify RNA binders from 77 678 protein binders from traditional medicinal chemistry programs (as identified in BindingDB).…”
Section: Forschungsartikelmentioning
confidence: 99%
“…The approach of using core RNA-binding scaffolds to identify targets of FDA-approved drugs was recently used to characterize palbociclib as a potent binder of the HIV TAR hairpin. [38] A separate approach also recently indicated that protein-targeting FDA approved drugs similar to known RNA binders can also have RNA-binding character. [39]…”
Section: Discussionmentioning
confidence: 99%
“…The approach of using core RNA-binding scaffolds to identify targets of FDA-approved drugs was recently used to characterize palbociclib as a potent binder of the HIV TAR hairpin. [38] A separate approach also recently indicated that proteintargeting FDA approved drugs similar to known RNA binders can also have RNA-binding character. [39] We also used LASSO logistic regression and neural networks to classify RNA binders from 77,678 protein binders from traditional medicinal chemistry programs (as identified in BindingDB).…”
Section: Discussionmentioning
confidence: 99%
“…Recent analyses have finally begun to address these questions, excitingly demonstrating that structurally diverse classes of small molecules, including drug-like small molecules ,,, and fragments, new classes of natural products, , and even known protein-targeted drugs like kinase inhibitors, can bind to RNAs, certainly challenging the notion that limited scaffolds reside within RNA-targetable chemical space. These discoveries have been made, in large part, due to technological advances in screening and chemical biology, aided by major advances in next-generation sequencing capabilities.…”
mentioning
confidence: 99%